Asymmetric Constriction of Dividing Escherichia coli Cells Induced by Expression of a Fusion between Two Min Proteins - Rowlett, Veronica Wells (American Society for Microbiology, 2014)
The Min system, consisting of MinC, MinD, and MinE, plays an important role in localizing the Escherichia coli cell division machinery to midcell by preventing FtsZ ring (Z ring) formation at cell poles. MinC has two domains, MinCn and MinCc, which both bind to FtsZ and act synergistically to inhibit FtsZ polymerization. Binary fission of E. coli usually proceeds symmetrically, with daughter cells at roughly 180° to each other. In contrast, we discovered that overproduction of an artificial MinCc-MinD fusion protein in the absence of other Min proteins induced frequent and dramatic jackknife-like bending of cells at division septa, with cell constriction predominantly on the outside of the bend. Mutations in the fusion known to disrupt MinCc-FtsZ, MinCc-MinD, or MinD-membrane interactions largely suppressed bending division. Imaging of FtsZ-green fluorescent protein (GFP) showed no obvious asymmetric localization of FtsZ during MinCc-MinD overproduction, suggesting that a downstream activity of the Z ring was inhibited asymmetrically. Consistent with this, MinCc-MinD fusions localized predominantly to segments of the Z ring at the inside of developing cell bends, while FtsA (but not ZipA) tended to localize to the outside. As FtsA is required for ring constriction, we propose that this asymmetric localization pattern blocks constriction of the inside of the septal ring while permitting continued constriction of the outside portion.